PENGARUH PAJAK HIBURAN TERHADAP PENDAPATAN ASLI DAERAH DI KOTA KEDIRI - Nindya Dana Charisma; Subagyo Subagyo; Moh. Zuhri Fathoni (POLITEKNIK CAHAYA SURYA, 2018)
Revenue can be derived from local revenues, local revenues arising from the distribution of local revenues, financial balancing funds between the central government and local governments, regional lending and other regional revenues.The purpose of this study is to know the entertainment tax in the City of Kediri, to know the influence of entertainment tax on the original revenue area in the city of Kediri. The data source obtained by the writer is the secondary data. The type of research used is descriptive quantitative.Data obtained from literature study and documentation.Data analysis method used in this research is descriptive analysis, correlation analysis, linear regression test and test.From the result of this study there is a significant income from entertainment taxes for the local revenue in the city of Kediri in 2012-2016.The entertainment tax on the local income in Kediri has a very high relationship, the higher revenue of the entertainment tax, the higher income the local revenue in Kediri and the lower revenue of the entertainment tax, the lower income of the original income of Kediri. Keywords: Entertainment tax, Local Revenue.income